Circle of Willis variations in migraine patients with ischemic stroke. Issue 3 (16th February 2019) - Hamming, Arend M.; van Walderveen, Marianne A. A.; Mulder, Inge A.; van der Schaaf, Irene C.; Kappelle, L. Jaap; Velthuis, Birgitta K.; Ferrari, Michel D.; Terwindt, Gisela M.; Visser, Marieke C.; Schonewille, Wouter; Algra, Ale; Wermer, Marieke J. H.; et al.
Abstract: Objectives: Migraine is a risk factor for stroke, which might be explained by a higher prevalence in anatomical variants in the circle of Willis (CoW). Here, we compared the presence of CoW variants in patients with stroke with and without migraine. Materials and Methods: Participants were recruited from the prospective Dutch acute Stroke Study. All participants underwent CT angiography on admission. Lifetime migraine history was assessed with a screening questionnaire and confirmed by an interview based on International Classification of Headache Disorders criteria. The CoW was assessed for incompleteness/hypoplasia (any segment <1 mm), for anterior cerebral artery asymmetry (difference > 1/3), and for posterior communicating artery (Pcom) dominance (Pcom–P1 difference > 1/3). Odds ratios with adjustments for age and sex (aOR) were calculated with logistic regression. Results: We included 646 participants with stroke, of whom 52 had a history of migraine. Of these, 45 (87%) had an incomplete or hypoplastic CoW versus 506 (85%) of the 594 participants without migraine (aOR: 1.47; 95% CI: 0.63–3.44). There were no differences between participants with and without migraine in variations of the anterior or posterior CoW, anterior cerebral artery asymmetry (aOR: 0.86; 95% CI: 0.43–1.74), or Pcom dominance (aOR: 0.64; 95% CI: 0.32–1.30). There were no differences in CoW variations between migraine patients with or without aura. Conclusion: We found no significant difference in the completeness of the CoW in acute stroke patients with migraine compared to those without. Abstract : Migraine is a risk factor for stroke, which might be explained by a higher prevalence in anatomical variants in the circle of Willis (CoW). We investigated this in 646 stroke patients, of whom 52 with migraine. Anatomical variations in the circle of Willis were equally common in stroke patients with or without a history of migraine, which does not support the theory that CoW variations play a role in migraine pathophysiology.